2016
DOI: 10.1186/s12864-016-2660-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined physiological, transcriptome, and cis-regulatory element analyses indicate that key aspects of ripening, metabolism, and transcriptional program in grapes (Vitis vinifera L.) are differentially modulated accordingly to fruit size

Abstract: BackgroundIn wine grape production, management practices have been adopted to optimize grape and wine quality attributes by producing, or screening for, berries of smaller size. Fruit size and composition are influenced by numerous factors that include both internal (e.g. berry hormone metabolism) and external (e.g. environment and cultural practices) factors. Combined physiological, biochemical, and transcriptome analyses were performed to improve our current understanding of metabolic and transcriptional pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 98 publications
(78 reference statements)
4
52
0
Order By: Relevance
“…Berry transcriptomics has been widely used to study this diversity. Differential expression under contrasting conditions and coexpression networks have suggested candidate genes for developmental changes (Carbonell‐Bejerano et al ., ; Cramer et al ., ; Palumbo et al ., ; Wong et al ., ), responses to stimuli (Deluc et al ., ; Rienth et al ., ; Blanco‐Ulate et al ., ), and variation in metabolite composition (Dal Santo et al ., ; Zenoni et al ., ). Gene expression is usually analysed in one or a few genotypes per experiment, and genotypes usually differ between experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Berry transcriptomics has been widely used to study this diversity. Differential expression under contrasting conditions and coexpression networks have suggested candidate genes for developmental changes (Carbonell‐Bejerano et al ., ; Cramer et al ., ; Palumbo et al ., ; Wong et al ., ), responses to stimuli (Deluc et al ., ; Rienth et al ., ; Blanco‐Ulate et al ., ), and variation in metabolite composition (Dal Santo et al ., ; Zenoni et al ., ). Gene expression is usually analysed in one or a few genotypes per experiment, and genotypes usually differ between experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of the grapevine genome and the rapid accumulation of publicly available grapevine whole-genome microarray and RNA-seq datasets provide the raw material necessary for GCN and CRE analyses. To date, several studies have utilized GCN and CRE analyses in revealing biologically relevant target genes of grapevine TFs 28–30 and/or providing clues into the regulatory relationships of TFs in key metabolic and ripening pathways 31 , 32 . However, to date no study has characterized grapevine promoter architecture and identified putative CRE regulatory modules at a genome-wide scale.…”
Section: Introductionmentioning
confidence: 99%
“…Since seed traces of stenospermocarpic cultivar are considered the primary source of GA in the grape berry after endosperm abortion (Conde et al, 2007), it was envisioned that berry variations in bioactive GA content may be influenced by differences in size or presence of seed traces. Analyses of 100 30-day-old berries, sampled randomly from 20 clusters, revealed the presence of seed traces in all berries of SB, while berries of BF had no visible seed traces.…”
Section: Resultsmentioning
confidence: 99%
“…In berries, however, both growth response to PAC and endogenous bioactive GA measurements correlated with the response to GA. As suggested above, the lower level of GA in BF, which may further contribute to its high response to GA application, can be associated to the absence of seed traces, which are the main sources of bioactive GAs in stenospermocarpic cultivars (Conde et al, 2007). In agreement with this hypothesis, (1) the absence of seed traces in BF correlated with low levels of bioactive GA (both GA 1 and GA 4 ) in the berries; (2) the presence of seed traces in the berries of SB was accompanied by higher bioactive GA 4 quantities, possibly resulting from the upregulation of GA biosynthetic genes, VvGA20ox4 and VvGA3ox3 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%